The Perception of UINSU Students towards GO-JEK Online Transportation Services - Anang Anas Azhar; Tri Ayu Andani Nasution (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
This study aims to determine the perception of Communication Science students of State Islamic University of North Sumatera (UINSU) Medan regarding the quality of services that are owned by GO-JEK Online. The theoretical framework used is new media theory, perception and service quality. This type of research uses methods descriptive quantitative research. The results showed that Communication Science students at Faculty of Social Sciences UINSU Medan had perceived GO-JEK as a good and credible online transportation. It can be seen from the results of physical appearance data, reliability, responsiveness, competence, politeness, credibility, security, access, communication and understanding have been stated well and good by users or consumers of GO-JEK. The results show an average of 79.37%. In terms of reliability which includes the extent to which information is obtained, it is stated that GO-JEK riders will take passengers to their destination make passengers wait a long time.